Pairing cells of different sizes in a microfluidic device for immunological synapse monitoring. Issue 5 (31st January 2022) - Shaik, Faruk Azam; Lewuillon, Clara; Guillemette, Aurélie; Ahmadian, Bahram; Brinster, Carine; Quesnel, Bruno; Collard, Dominique; Touil, Yasmine; Lemonnier, Loïc; Tarhan, Mehmet Cagatay
Abstract : A cell pairing method is developed to monitor immunological synapses formed by single cells with different sizes. Abstract : Analyzing cell–cell interaction is essential to investigate how immune cells function. Elegant designs have been demonstrated to study lymphocytes and their interaction partners. However, these devices have been targeting cells of similar dimensions. T lymphocytes are smaller, more deformable, and more sensitive to pressure than many cells. This work aims to fill the gap of a method for pairing cells with different dimensions. The developed method uses hydrodynamic flow focusing in the z -direction for on-site modulation of effective channel height to capture smaller cells as single cells. Due to immune cells' sensitivity to pressure, the proposed method provides a stable system without any change in flow conditions at the analysis area throughout experiments. Paired live cells have their activities analyzed with calcium imaging at the immunological synapse formed under a controlled environment. The method is demonstrated with primary human T lymphocytes, acute myeloid leukemia (AML) cell lines, and primary AML blasts.